Challenges in accessing maternal and child health services during COVID-19 and the potential role of social networking technologies. (March 2022) - Musiimenta, Angella; Tumuhimbise, Wilson; Atukunda, Esther C; Ayebaza, Sandrah; Kobutungi, Phionah; Mugaba, Aaron T; Asasira, Justus; Mugyenyi, Godfrey R; Katusiime, Jane; Zender, Raphael; Pinkwart, Niels; Haberer, Jessica E
Background: The COVID-19 pandemic causes new challenges to women and their babies who still need to access postnatal care amidst the crisis. The novel application of social network technologies (SNTs) could potentially enhance access to healthcare during this difficult time. Objectives: This study describes the challenges experienced in accessing maternal and child health services by women with limited or no education during this COVID-19 pandemic and discusses the potential of SNTs to support maternal and child health amidst this crisis. Methods: We administered surveys to women who had recently given birth in a rural setting and interviewed a purposively selected subset to ascertain their experiences of accessing maternal and child health services during the COVID-19 pandemic. Our analysis involved descriptive analysis of quantitative data using STATA 13 to describe study participants' characteristics, and content analysis of qualitative data to derive categories describing maternal health challenges. Results: Among 50 women, the median age was 28 years (interquartile range 24–34), 42 (84%) completed upper primary education. Access to the health facility was constrained by transport challenges, fear of contracting COVID-19, and delays at the facility. Due to the COVID-19 crisis, 42 (84%) women missed facility visits, 46 (92%) experienced financial distress, 43 (86%) had food insecurity, and 44 (88%) felt stressed. SNTs can facilitate remote and timely access to health services and information, and enable virtual social connections and support. Conclusion: SNTs have the potential to mitigate the challenges faced in accessing maternal and child health services amidst the ongoing COVID-19 pandemic.